2018
DOI: 10.3389/fphys.2018.01180
|View full text |Cite
|
Sign up to set email alerts
|

The Diurnal Timing of Starvation Differently Impacts Murine Hepatic Gene Expression and Lipid Metabolism – A Systems Biology Analysis Using Self-Organizing Maps

Abstract: Organisms adapt their metabolism and draw on reserves as a consequence of food deprivation. The central role of the liver in starvation response is to coordinate a sufficient energy supply for the entire organism, which has frequently been investigated. However, knowledge of how circadian rhythms impact on and alter this response is scarce. Therefore, we investigated the influence of different timings of starvation on global hepatic gene expression. Mice (n = 3 each) were challenged with 24-h food deprivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…The expression of many clock genes was also differently affected by differently timed starvation. 24 According to our paradigm that clock and Hh signaling closely interact we show herein that components of the Hh signaling cascade are also differently affected by the different timing of starvation. As depicted in Fig.…”
Section: Simultaneous Changes Of Clock and Hh Genes Induced By Starvamentioning
confidence: 70%
See 1 more Smart Citation
“…The expression of many clock genes was also differently affected by differently timed starvation. 24 According to our paradigm that clock and Hh signaling closely interact we show herein that components of the Hh signaling cascade are also differently affected by the different timing of starvation. As depicted in Fig.…”
Section: Simultaneous Changes Of Clock and Hh Genes Induced By Starvamentioning
confidence: 70%
“…In a recent study we have shown that different timing of starvation of C57BL/6N mice results in completely different metabolic responses over a 24 h period. 24 Starvation induced in the morning at ZT3 resulted in the well-known response characterized by induced gluconeogenesis, while starvation induced in the evening at ZT15 caused a completely different response involving downregulation of gluconeogenesis and increased fatty acid and cholesterol synthesis. The expression of many clock genes was also differently affected by differently timed starvation.…”
Section: Simultaneous Changes Of Clock and Hh Genes Induced By Starvamentioning
confidence: 99%
“…(responsible for glycogen storage (Akman et al, 2011;Iijima et al, 2018)), were uniquely upregulated in IF16 and EOD, respectively. However, in both IF16 and EOD common genes, such as Elovl2 (involved in de novo lipogenesis, lipid storage, and subsequent fat mass expansion (Pauter et al, 2014;Rennert et al, 2018)) and…”
Section: Discussionmentioning
confidence: 99%
“…For the South African clawed toad Xenopus laevis, its liver glycogen levels were reduced by 80-90% after 12 months of starvation at 20 • C (Merkle and Hanke, 1988). For other vertebrates, several studies showed that genes involved in ketogenesis, gluconeogenesis, and fatty acid beta-oxidation, were up-regulated in liver of chicken after 16 h of starvation (Desert et al, 2008), in liver of mice after 24 h of starvation (Kinouchi et al, 2018;Rennert et al, 2018), in liver of fishes after 21 days of starvation (Drew et al, 2008;Qian et al, 2016). Compared to other vertebrates, the hypogean salamanders exhibited remarkable resistance to long periods of food deprivation, this may be due to the remarkable accumulation of lipid and glycogen deposits in the liver, and glycogen level maintenance during food deprivation.…”
Section: Introductionmentioning
confidence: 99%